Assessing the reproducibility and validity of a food frequency questionnaire for pregnant women from the Chinese Miao ethnic group - Ni, Xiaorong; Qiao, Tian; Wang, Rong; Wang, Fang; Liang, Yi; Wei, Shaofeng (Frontiers in Nutrition, 2024)
Background Currently, no food frequency questionnaire is available for ethnic minorities in China.This study aimed to evaluate the reproducibility and validity of a culturally tailored semi-quantitative Food Frequency Questionnaire (FFQ) designed for pregnant women of the Miao ethnic group in China. Methods A total of 74 FFQ questions were administered to collect dietary information during pregnancy from Miao women in China. The validity and reproducibility of this study included 153 and 127 pregnant women, respectively. Baseline FFQ data (FFQ1) were collected initially, followed by the administration of a repeated FFQ 4-6 weeks later (FFQ2). Two 24-hour recalls (24HR) were used as references to compare food groups and nutrient intake. Pearson/Spearman's coefficients were used to measure the validity and reproducibility of the FFQ. Quartile cross-classification, weighted kappa coefficients, and Bland-Altman plots were employed to assess agreement. Results Most food groups and nutrient intake estimated by the FFQ were higher than those estimated by the 24HR. Food groups and nutrients' correlations for FFQ vs. 24HR after being energy-adjusted and de-attenuated, respectively, were 0.10 (vegetables) to 0.45 (grains/tubers) and 0.15 (iron) to 0.52 (riboflavin).Comparatively, correlation coefficients for FFQ1 vs. FFQ2 ranged from 0.41 (fruit) to 0.71 (vegetables) and 0.45 (energy) to 0.64 (calcium). The percentage of pregnant women classified in the same or adjacent quartiles ranged from 64.08% (vegetables) to 95.29% (sour soup) and 68.88%(vitamin E) to 78.81% (energy). Weighted kappa coefficients exceeded 0.2 for food groups and most nutrients, and Bland-Altman plots demonstrated acceptable agreement between the two tools.This study provides novel information on the validation results of the FFQ. It demonstrates that the FFQ exhibits ideal reproducibility and acceptable validity in estimating and ranking the intake of food groups and most nutrients among Chinese Miao pregnant women.